2016
DOI: 10.1016/j.eururo.2015.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for Men with Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: count 298Key words: Exercise, prostate cancer, quality of life, fatigue, adverse effects AbstractContext: Exercise for prostate cancer survivors could be beneficial. However, no systematic review across cancer stages and treatment types addressing potential benefits and harms exists to date.Objectives: Primarily, to assess the effects of exercise on cancer specific quality of life and adverse events in prostate cancer trials. Evidence acquisition:We searched the Cochrane Central Register of Controlled Trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
213
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(231 citation statements)
references
References 43 publications
13
213
0
5
Order By: Relevance
“…In endometrial, ovarian and colorectal cancer survivors, lifestyle interventions that include regular participation in physical activity are associated with positive health outcomes (45,46). Furthermore, it has been demonstrated that individuals who are physically active after being diagnosed with breast or colon cancer exhibit a higher rate of survival compared with those that are physically inactive (47).…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial, ovarian and colorectal cancer survivors, lifestyle interventions that include regular participation in physical activity are associated with positive health outcomes (45,46). Furthermore, it has been demonstrated that individuals who are physically active after being diagnosed with breast or colon cancer exhibit a higher rate of survival compared with those that are physically inactive (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, although recent meta-analysis has reported the benefit of exercise therapy on the cancer-specific quality of life and fatigue [7] in PCa patients, available data about the feasibility of exercise is still inconsistent. The purpose of this meta-analysis is to evaluate the role of exercise in control mental and physical changes in PCa patients receiving ADT and analyze whether the duration and the type of exercise correlate with the effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a systematic review and meta-analysis support the hypotheses that exercise approaches improve PCa-related quality of life and fatigue, submaximal physical fitness, and lower body strength (31). Another review involving observational epidemiological studies has shown associations between physical activity and PCa risk.…”
Section: Discussionmentioning
confidence: 58%